THU0509 IMPACT OF PEDIATRIC RHEUMATIC DISEASES ON MEXICAN CAREGIVERS. (2nd June 2020) - Fortuna, B.; Peláez-Ballestas, I.; García-Rodríguez, F.; Faugier, E.; Mendieta, S.; Villlarreal, A. V.; Rosiles, S.; Reyes, G.; Jimenez, S.; Guadarrama, J.; Rubio, N.
Abstract : Background: Pediatric rheumatic diseases (PRD) have an important impact on different aspects of the patients' and caregivers' life, such as physical, emotional, economic, and social. Some studies have shown that parents of patients with PRD have important impact but there is a lack of information of this topic from Latinamerican countries. Objectives: The aim of this study is to describe and analyze the impact of juvenile idiopathic arthritis (JIA), juvenile systemic lupus erythematosus (JSLE), and juvenile dermatomyositis (JDM) on Mexican primary caregivers. Methods: This is a multicenter cross-sectional study conducted in third-level reference pediatric hospitals in Mexico from December 2018 to November 2019. We included primary caregivers of pediatric patients with JIA, JSLE, and JDM that were treated in participant centers. CAREGIVERS questionnaire, a validated multiassesment tool to measure the impact of PRD on caregivers, was applied to the participants. Collection of social, demographic, and clinical data was also performed and correlated with questionnaire results. Results: A total of 200 primary caregivers participates in the study (109 JIA, 28 JDM, and 63 JSLE), aged 38 (IQR 32 – 46), mostly women (84.5%), from 6 centers, representing 13/32 Mexican states (Figure ). One third (78) had a remunerated job, 123 (61.5%) had a relationship, 77 (38.5%) reached high school or higher, and 131 (65.5%) spends more than one hour to get to the center. Patients cared aged 12 (IQR 9 – 16), mostly women (67%), 87 (43.5%) with active disease, 43 (21.5%) with any disability, 94% and 29% treated with DMARD and biologics, respectively. Feelings of worry and sadness predominant at diagnosis that decreased over time (42.5% and 28.5% vs 9.5% and 31.5%, respectively) and changed for peace (44%). Concerns about disabilities were more frequent on JIA group (34%), while pain and economic issues in JSLE (47% and 30%, respectively. Most of the caregivers feel anxiety about the future of their patients (148, 74%), regardless of the diagnosis. Participants reported that the way they spend the time, social life, and personal health worsened since diagnosis (49.5%, 32%, and 34.5%, respectively), especially in those with JSLE (60%, 39%, 46%). In 126 (63%) participants the economic situation worsened, 129 (64.5%) borrowed money (76% in JSLE, P = .03), 63 (31.5%) had problems to buy medications, and 48.5% have had problems at work. In 25 (12.5%), the family relationship was affected after diagnosis, however, the main supportive network reported were family members. Conclusion: This work described the main impacted areas in life of primary caregivers of patients with PRD, showing a perspective of the burden of the disease. References: [1]Cohen EM. Pediatr Rheumatol [Internet]. Pediatric Rheumatology; 2017;15(1):6. [2]Torres-Made. Pediatr Rheumatol 18, 3 (2020). Disclosure of Interests: None declared